Systemic autoimmune diseases in patients with hepatitis C virus infection: characterization of 1020 cases (The HISPAMEC Registry). (2009)
Objective. To describe the clinical and immunologic characteristics of a large series of patients with systemic autoimmune diseases (SAD) associated with chronic hepatitis C virus (HCV) infection. Methods. The HISPAMEC Registry is a multicenter international study group dedicated to collecting data on patients diagnosed with SAD with serological evidence of chronic HCV infection. The information sources are cases reported by physicians of the HISPAMEC Study Group and periodic surveillance of reported cases by a Medline search updated up to December 31, 2007. Results. One thousand twenty HCV patients with SAD were included in the registry. Patients were reported from Southern Europe (60%), North America (15%), Asia (14%), Northern Europe (9%), South America (1%), and Australia (1%). Countries reporting the most cases were Spain (236 cases), France (222 cases), Italy (144 cases), USA (120 cases), and Japan (95 cases). The most frequently reported SAD were Sjögren’s syndrome (SS; 483 cases), rheumatoid arthritis (RA; 150 cases), systemic lupus erythematosus (SLE; 129 cases), polyarteritis nodosa (78 cases), antiphospholipid syndrome (59 cases), inflammatory myopathies (39 cases), and sarcoidosis (28 cases). Twenty patients had 2 or more SAD. Epidemiological data were available in 677 cases. Four hundred eighty-seven (72%) patients were female and 186 (28%) male, with a mean age of 49.5 ± 1.0 years at SAD diagnosis and 50.5 ± 1.1 years at diagnosis of HCV infection. The main immunologic features were antinuclear antibody (ANA) in 61% of patients, rheumatoid factor (RF) in 57%, hypocomplementemia in 52%, and cryoglobulins in 52%. The main differential aspect between primary and HCV-related SAD was the predominance of cryoglobulinemic-related markers (cryoglobulins, RF, hypocomplementemia) over specific SAD-related markers (anti-ENA antibodies, anti-dsDNA, anti-cyclic citrullinated peptide) in patients with HCV. Conclusion. In the selected cohort, the SAD most commonly reported in association with chronic HCV infection were SS (nearly half the cases), RA and SLE. Nearly two thirds of SAD-HCV cases were reported from the Mediterranean area. In these patients, ANA, RF and cryoglobulins are the predominant immunological features. (First Release April 15 2009; J Rheumatol 2009;36:1442–8; doi:10.3899/jrheum.080874).